Insulin secretion defects of human type 2 diabetic islets are corrected in vitro by a new reactive oxygen species scavenger - Lupi, R.; Del Guerra, S.; Mancarella, R.; Novelli, M.; Valgimigli, L.; Pedulli, G.F.; Paolini, M.; Soleti, A.; Filipponi, F.; Mosca, F.; Boggi, U.; Del Prato, S.; et al. (Diabetes & metabolism, 2007)
Oxidative stress is a putative mechanism leading to beta-cell damage in type 2 diabetes. We studied isolated human pancreatic islets from type 2 diabetic and non-diabetic subjects, matched for age and body mass index. Evidence of increased oxidative stress in diabetic islets was demonstrated by measuring nitrotyrosine concentration and by electron paramagnetic resonance. This was accompanied by reduced glucose-stimulated insulin secretion, as compared to non-diabetic islets (Stimulation Index, SI: 0.9 ± 0.2 vs. 2.0±0.4, P < 0.01), and by altered expression of insulin (approximately –60%), catalase (approximately +90%) and glutathione peroxidase (approximately +140%). When type 2 diabetic islets were pre-exposed for 24 h to the new antioxidant bis(1-hydroxy-2,2,6,6-tetramethyl-4-piperidinyl)decandioate di-hydrochloride, nitrotyrosine levels, glucose-stimulated insulin secretion (SI: 1.6 ± 0.5) and gene expressions improved/normalized. These results support the concept that oxidative stress may play a role in type 2 diabetes beta-cell dysfunction; furthermore, it is proposed that therapy with antioxidants could be an interesting adjunctive pharmacological approach to the treatment of type 2 diabetes. Le stress oxydant est considéré un mécanisme important à l'origine des lésions des cellules β dans le diabète type 2. Dans des îlots humains isolés à partir de sujets diabétiques type 2 et non diabétiques, comparables par âge et le BMI, l'augmentation du stress oxydatif a été mise en évidence par l'évaluation des concentrations de nitrotyrosine et par résonance paramagnétique électronique. Par ailleurs, chez les îlots diabétiques, a été mise en évidence une réduction de la sécrétion d'insuline induite par le glucose par comparaison aux îlots témoins, avec en outre, une expression anormale de l'insuline (~ –60